Mpimanyiso wa masungulelo ya ndyangu wa ndhavuko na wa manguva lawa wa vatsonga - Ngobeni, T. P. (My University, 2019)
My study investigates the establishment of a family institution with special reference to Vatsonga.The study will focus on comparing the traditional with modern ways of establishing a family institution. The study aims at investigating values and principles behind strong foundations upheld by old people regarding families. The study could lay a foundation for scholars’ further investigative studies on establishment of African traditional families. The study will serve as a reference in times of family crisis for potential readers. It is going to employ a qualitative research approach where unstructured interviews will be used to engage participants with relevant information. The study will engage twelve participants (six male and six female) elderly people who have experience in traditional family establishment whose ages range from fifty-five and above. It will be conducted around Malamulele area in Vhembe District of Limpopo and it will be conducted in Xitsonga.
A comparative study of the establishment of a traditional and the modern vatsonga families
Thesis (M. A.) -- University of Limpopo, 2019
Keywords: Tsonga families; Family establishment; Tsonga tradition; Families; Domestic relations